2019
DOI: 10.19030/jbcs.v15i1.10282
|View full text |Cite
|
Sign up to set email alerts
|

Water Crisis In Flint Michigan – A Case Study

Abstract: This case study is designed to provide detailed information about the water crisis in Flint, Michigan brought on by a series of decisions that could have been researched better prior to enactment. The results were catastrophic to the citizens that public officials were sworn to protect. This case study will provide university classes with information to use while analyzing the causes and decisions that lead to the Flint Water Crisis. This study is not designed to provide all information, but to supplement clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In this sense, CRS calls for agency and advocacy for equitable representation of those who may not have the capacity to represent themselves. For example, in Flint, Michigan, lead poisoning from contaminated water is associated with elevated blood lead levels in children (Day et al, 2019; Forrer et al, 2019; Hanna-Attisha et al, 2016; see Table 2). Laidlaw et al (2016) found that most low-income and minority students in Flint had high levels of lead in their blood (Laidlaw et al, 2016), which affects school achievement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, CRS calls for agency and advocacy for equitable representation of those who may not have the capacity to represent themselves. For example, in Flint, Michigan, lead poisoning from contaminated water is associated with elevated blood lead levels in children (Day et al, 2019; Forrer et al, 2019; Hanna-Attisha et al, 2016; see Table 2). Laidlaw et al (2016) found that most low-income and minority students in Flint had high levels of lead in their blood (Laidlaw et al, 2016), which affects school achievement.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Table 2, the population demographics of Flint are predominantly African American, particularly in the city limits where high levels of lead are found in drinking water (Forrer et al, 2019). Lead poisoning and contaminated waters are also associated with intestinal track diseases and diarrhea.…”
Section: Toxic Watermentioning
confidence: 99%